2018
DOI: 10.5653/cerm.2018.45.3.116
|View full text |Cite
|
Sign up to set email alerts
|

Associations of serum fetuin-A and oxidative stress parameters with polycystic ovary syndrome

Abstract: ObjectiveThe aim of this study was to compare serum fetuin-A levels and oxidative stress markers, as indicators of insulin resistance, in women with polycystic ovary syndrome (PCOS) and in healthy controls.MethodsThis prospective case-control study included 46 patients with PCOS and 48 age- and body mass index–matched control women. Levels of serum hormones, fetuin-A, and oxidative stress markers were measured in blood samples taken during the early follicular period from each participant.ResultsFollicle-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
8
17
1
Order By: Relevance
“…In the current investigate, we found that circulating Fetuin-A concentrations were markedly elevated in PCOS women compared with healthy women. Our results are consistent with those of Enli et al [28,[30][31], but contrary to those of Díaz et al [20]. The cross-sectional nature of studies and population heterogeneity in women with PCOS may be related to differences in outcomes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the current investigate, we found that circulating Fetuin-A concentrations were markedly elevated in PCOS women compared with healthy women. Our results are consistent with those of Enli et al [28,[30][31], but contrary to those of Díaz et al [20]. The cross-sectional nature of studies and population heterogeneity in women with PCOS may be related to differences in outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…However, the conclusions of these studies are contradictory. In previous studies, circulating Fetuin-A levels were increased, decreased or unchanged in PCOS patients compared with normal women [20,[27][28][29][30][31]. In the current investigate, we found that circulating Fetuin-A concentrations were markedly elevated in PCOS women compared with healthy women.…”
Section: Discussionsupporting
confidence: 60%
“…In the current investigation, we found that circulating Fetuin-A concentrations were markedly elevated in women with PCOS compared to healthy women. Our results are consistent with those of Enli et al [33][34][35], but contrary to those of Díaz et al [22]. The cross-sectional nature of the study and population heterogeneity may be related to differences in outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…However, the conclusions of these studies are contradictory. In previous studies, circulating Fetuin-A levels were increased, decreased or unchanged in PCOS patients compared with normal women [22,[31][32][33][34][35]. In the current investigation, we found that circulating Fetuin-A concentrations were markedly elevated in women with PCOS compared to healthy women.…”
Section: Discussionsupporting
confidence: 59%
“…Kidney and liver tissues were washed with saline at +4 °C, dried on blotting paper and stored in 1 ml storage vials and stored in deep freezer (-80 °C) until analyses were performed. Before the analyses, renal and liver tissues were homogenized using a homogenizer (Stuart, SHM1/ EURO, UK) by adding (10 %, w/v) 140 mM KCl solution at +4 °C (10). The obtained homogenates were centrifuged at 3000 rpm for 5 minutes at +4 °C.…”
Section: Biochemical Analysismentioning
confidence: 99%